Histopathological pattern of solid malignant pediatric tumors in Kashmir, India - Wani, Lateef Ahmed; Farooq, Summyia; Beigh, Ambreen; Khuroo, Mehnaaz; Abass, Farhat (International Journal of Contemporary Pediatrics, 2018)
Background: Tumors that occurs in children are as diverse as those in adults and present a number of challenges for the pathologist. In general, the features of malignancies in children differ biologically and histologically from those of adults with respect to incidence, type of tumor, underlying familial or genetic aberration and tendency to regress spontaneously or cytodifferentiation. The objective of study was to the study was carried out to document pattern of childhood malignant tumors in Kashmir and compare with other studies from other parts of country. Methods: The records of all the tumors diagnosed histopathologically in children <15 years of age during a period of 3-year (2014 to 2017) in pathology department of Government Medical College Srinagar. The sections 3-5 μ thick, are cut and stained by haematoxylin and eosin in all cases and special stains where ever feasible. Results: A total of 46 tumors were seen in the age range of 2 month to 14 years with 26 (56.52%) in boys and 20 (43.47) in girls. Highest number of cases, 23 (50%) were in the age group of 0-5 years. Lymphomas and retinoblastoma were most common child hood malignancies followed by soft tissue tumors and CNS tumors. Conclusions: Although the exact incidence rate cannot be provided by this hospital-based study, the information is useful in showing patterns of childhood tumors. Documentation of cases, advanced diagnostic methods like IHC, cytogenetic studies and treatment modalities with close follow up is needed to achieve better outcome.